Theoretical Aspects of Accounting the Wear of Wheeled Vehicles When Assessing the Damage Caused to Them as a Result of Deterioration - I. N. Novoseletskii; S. V. Fedotov (Теория и практика судебной экспертизы)
The article is devoted to the problem of the validity of determining the wear of component parts when calculating the damage caused to a vehicle due to its deterioration. The authors address the legal line of arguments of the differentiated approach when deciding on the need to consider wear and tear. They also make suggestions on its practical reflection in forensic expert opinions. Finally, it is highlighted that when making decisions regarding wear and tear, it is essential to consider the method of compensation for damage caused and official legal information.The authors justify the necessity to use the provisions of the methodological recommendations developed in the Federal State Budgetary Institution of the Russian Federation under the Ministry of Justice of the Russian Federation in the calculations, which will allow experts to formulate categorical and not relative or multivariate conclusions.